Pure Red Cell Aplasia Following Interleukin-2 Therapy. (11th April 2016) - Dutcher, Janice P.; Fan, Wen; Wiernik, Peter H.
A 61-year-old woman with metastatic renal cell carcinoma underwent systemic treatment with high-dose interleukin-2 (IL-2). Anemia requiring transfusion of 1 unit of packed red blood cells (PRBCs) was required during the second week of IL-2 therapy. One month following completion of high-dose IL-2 treatment, she was hospitalized for severe, symptomatic anemia and received 5 units of PRBCs. She was referred back for evaluation. A complete hematologic evaluation was performed including antiviral serology, evaluation for hemolysis, complete iron studies, and finally bone marrow aspiration and biopsy. The diagnosis was pure red cell aplasia, and no inciting viral cause could be ascertained. She required PRBCs for 5 months following IL-2 therapy. It was concluded that IL-2 was the cause of her red cell aplasia. This subsequently resolved spontaneously, and she had normal hemoglobin and hematocrit, respectively, 1 and 2 years after treatment.